Mass transfer with chemical reaction on flow past an accelerated vertical plate with variable temperature and thermal radiation - Muthucumaraswamy, Rajamanickam; Balachandran, P.; Ganesan, K. (Zielona Góra: Uniwersytet Zielonogórski)
An exact solution of an unsteady radiative flow past a uniformly accelerated infinite vertical plate with variable temperature and mass diffusion is presented here, taking into account the homogeneous chemical reaction of first order. The plate temperature as well as concentration near the plate is raised linearly with time. The dimensionless governing equations are solved using the Laplace-transform technique.
Keywords: linearly accelerated; chemical reaction; radiation; heat transfer; mass transfer